2011
DOI: 10.1177/0192623311418680
|View full text |Cite|
|
Sign up to set email alerts
|

RETRACTED: Role of Quercetin in Preventing Thioacetamide-Induced Liver Injury in Rats

Abstract: In hepatic toxicity induced in rats by two injections of thioacetamide (TAA, 350 mg/kg with an interval of 8 hr), the action of quercetin was investigated. After 96 hr, TAA administration resulted in hepatic necrosis, significant increases in serum transaminase activity, and increases in hepatic lipoperoxidation. Thioacetamide-induced hepatotoxicity also showed changes in antioxidant enzymes in the liver of rats, with alterations in p-ERK 1/2 (phosphorylated extracellular-signal related kinase 1/2) as well as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
54
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 108 publications
(67 citation statements)
references
References 66 publications
11
54
0
2
Order By: Relevance
“…Vidhya and Indira 4 and Chen 5 describe a significant reduction in these enzymes with the use of quercetin in a rat model of ethanol-induced hepatic lesion. The same was observed by David et al 23 in an experimental model with thioacetamide. A recent work by El-Shafey et al 24 , in which oral quercetin was given to rats (15 mg/kg/day) during 21 days prior to a toxic dose of paracetamol, focused on many of the parameters assessed by us in the present study.…”
Section: Effects Of Quercetin On Paracetamol-induced Liver Damagesupporting
confidence: 86%
See 2 more Smart Citations
“…Vidhya and Indira 4 and Chen 5 describe a significant reduction in these enzymes with the use of quercetin in a rat model of ethanol-induced hepatic lesion. The same was observed by David et al 23 in an experimental model with thioacetamide. A recent work by El-Shafey et al 24 , in which oral quercetin was given to rats (15 mg/kg/day) during 21 days prior to a toxic dose of paracetamol, focused on many of the parameters assessed by us in the present study.…”
Section: Effects Of Quercetin On Paracetamol-induced Liver Damagesupporting
confidence: 86%
“…The duration of treatment and the administration route may interfere with the hepatoprotective effect of quercetin. Miltersteiner 3 , Bona et al 9 and David et al 23 found positive results with intraperitoneal administration of quercetin. Behling et al 6 and Bona et al 9 used periods of 28 days and six weeks respectively.…”
Section: Effects Of Quercetin On Partial Hepatectomymentioning
confidence: 96%
See 1 more Smart Citation
“…These findings were confirmed by histopthological examination. The findings of the present study are congruent to the previous studies [21,27,28,29]. Mechanisms participating in the development of TAA-induced liver injury have been intensively studied.…”
Section: Discussionsupporting
confidence: 92%
“…Various reports show that quercetin has neuro-protection, anti-tumor, antiinflammation, anti-oxidant, and anti-diabetic effects (Chirumbolo, 2010;Kelly, 2011;Dajas, 2012). Furthermore, some reports demonstrate that quercetin can ameliorate various toxin-induced liver injuries, such as ethanol and acetaminophen (Vicente-Sánchez et al, 2008;Liu et al, 2010;Yousef et al, 2010;de David et al, 2011;Domitrović et al, 2012). However, the concrete-engaged signals in regulating the protection of quercetin against liver injuries are not very clear.…”
Section: Introductionmentioning
confidence: 99%